CONTRIBUTION OF PETROGRAPHIC AND GEOCHEMICAL ANALYSES OF THE KIPALA SHALE (CENTRAL BASIN, DRC) TO THE ASSESSMENT OF ITS POTENTIAL AS A HYDROCARBON SOURCE ROCK - DJONIVE MUNENE ASIDI; FLEURY SIMBUNGU ANGBOKO; THOMAS KANIKA MAYENA; RUTH ILUNGA MULAJI; ANGE THIJENIRA LOKETO; FREDERIC MAKOKA MWANZA; LEVESQUE MAKUKU MBO; RACHIDI OPULUKU; JEAN IYOLO LUNGEMBO (Journal of Engineering Studies and Research)
A geological study of the Kipala region, in the "Cuvette Centrale" of the Democratic Republic of Congo, has identified two groups of shales: the dark greasy facies, interbedded with the brownish-gray facies. Their high Total Organic Carbon (TOC) content (11 % TOC on average for the dark greasy shales, compared with 8 % for the second group) classifies them as very good hydrocarbon source rocks, according to the criteria of Epistalie et al. Field and laboratory data suggest that the rocks studied were deposited in a lagoon connected to the sea by an intermittently closing channel.